OCCURRENCE OF LIPIDS IN THE LIVER OF THE HYPERTRIGLYCERIDEMIC RATS - Zemanova, Zdenka; Strnadova, Miluse; Jirsova, Zuzana; Klusonova, Petra (Biomedical papers, 2009)
AIMS: The purpose of this study was to demonstrate the accumulation and distribution of lipids in the liver of the adult Prague hereditary hypertriglyceridemic (HHTg) rats. They reveal an increased expression of 11β-hydroxysteroid dehydrogenase 1 (11HSD1), which locally increases concentration of corticosterone in the liver. We studied the effect of the 11HSD1 inhibition on the lipid content.METHODS: Samples of liver of three groups of adult female rats - HHTg, HHTg treated for 14 days with 50 mg/kg/day carbenoxolone (HHTg+CBX) and control Wistar rats, were examined histochemically. Cryosections of the samples were stained with Oil red O or Sudan black B to demonstrate different kinds of lipids. Extent and intensity of staining was evaluated semiquantitatively.RESULTS: The orientational analysis showed a higher extent and intensity of the staining of the liver of HHTg and HHTg+CBX rats (equal in both hypertriglyceridemic groups) than that of the control Wistar rats. Oil red O stained unsaturated fatty acids and neutral fats, mainly triglycerides. The difference was on average 30 per cent. Staining of phospholipids with Sudan black B showed similarly the higher positivity in the hypertriglyceridemic groups than in controls.CONCLUSIONS: Staining for triglycerides and phospholipids demonstrated a higher amount of lipids in the liver of HHTg and HHTg+CBX female rats than in controls. The inhibition of 11HSD1 activity had no effect on the lipid content in the liver of the HHTg rats.
Keywords: Lipid accumulation/Prague Hereditary Hypertriglyceridemic rats/Liver histochemistry/OilRed/Sudan Black/Local glucocorticoid metabolism